Upaya Meningkatkan Kedisiplinan Anak Usia 3-4 Tahun Melalui Simulasi Lalu Lintas - Susiyah, Susiyah; Subawi, Subawi (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to determine the discipline of children at KB Puri Siwi Tamansari Academic Year 2016/2017 and find out the improvement of children's discipline through playing traffic simulations at KB Puri Siwi Tamansari Academic Year 2016/2017. This research method uses a type of classroom action research. This research was conducted in two stages, namely cycle I and cycle II. The subjects of this study were Puri Siwi Play Group students aged 3-4 years Tamansari Tlogowungu Pati as many as 16 students. The results of this study indicate that traffic simulations to improve child discipline are carried out with two cycles, the first cycle is carried out by simulating traffic signs with micro equipment, sikus II is carried out by simulating traffic signs with macro equipment. The results of data analysis and observations through traffic simulations showed an increase from the pre-cycle of 30% of children who completed their discipline, rising in the first cycle to 56.7%. That is, an increase of 24%. And in the second cycle increased to 81% and an increase of 25%. The results achieved in the second cycle had met the intended completeness target, namely 80% of all children scored with a complete category of 85. This increase in the average value proved the success of traffic simulations can improve children's discipline.